Saturated and aromatic compounds of highly paraffinic oil and organic deposit - Natalia Gerasimova; Elena Kovalenko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The urgency of the discussed issue is caused by the necessity to obtain the detailed information on the content and composition of hydrocarbons and heteroatomic components in high-paraffinic oils and the asfalto-resin-parafin deposits formed of the latter to solve the problems of production and transport of nonconventional hydrocarbonic raw materials. The main aim of the study is to determine the features of distribution and structure of paraffin, naphthenic and aromatic hydrocarbons and aromatic sulfur-containing compounds in high-paraffinic oil and the organic deposit obtained from it. The methods used in the study: element analysis, liquid and adsorptive chromatography, gas chromatography-mass spectrometry. The results: The authors have determined the similarity of distribution and structure of certain types of saturated and aromatic compounds in oil components of high-paraffinic oil and organic deposit. It is shown that both samples contain identical homological ranks of n-alkanes (С10-С37), alkylcyclohexanes (С12-С25), alkylbenzenes (С15-С29), not replaced naphthalene, fhenantrene and dibenzothiofhene, and their alkyl derivative (С1-С4). (C12-C22)-alkanes, (C12-C25)-cyclohexanes, (C15-C17)-alkylbenzenes, C1-alkylnaftalin, C1-alkylphenanthrene and (C1-C2)-alkyldibenzothiophenes prevail among the identified compounds of both samples. Isomeric composition of the studied compounds is identical.